Pengaruh Partisipasi Demokrasi dalam Politik dan Transisi Energi terhadap Impor Beras Indonesia - Arya Bima Wikantyasa; Inda Fresti Puspitasari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study examines the effects of democratic participation and energy transition on rice imports in Indonesia during 2010–2023 on a quarterly basis. Quarterly data were derived from annual data conversion and temporal disaggregation for volatile variables. A quantitative approach employing the Autoregressive Distributed Lag (ARDL) bound test was applied to estimate short- and long-term impacts. ARDL–ECM results indicate a strong short-term correction mechanism, with approximately 64% of deviations from long-term equilibrium adjusted within one quarter. Democratic participation exerts a significant negative effect on short-term rice imports, highlighting the role of political institutions in enhancing food self-sufficiency, while inflation shows a significant positive effect, reflecting the use of imports as a price stabilization tool. In the long term, most variables are not significant except for international rice prices, indicating the vulnerability of Indonesia’s imports to global market fluctuations. CUSUM and CUSUMSQ tests confirm model stability. These findings emphasize that political institutions influence short-term food policy, yet limited institutional capacity maintains long-term dependence on global prices.